Evaluasi Kualitas Aplikasi DJP Online Terhadap Kepuasan Pengguna Dengan Metode EUCS Dan IPA - Rani Febyanti Prasetyaningrum; Zaidatun Ekastuti (Jurnal Aplikasi Perpajakan, 2025)
Along with the digitalization of public services, the DJP Online application has become an important tool for taxpayers, especially MSMEs, in fulfilling their tax obligations. This study aims to evaluate the level of satisfaction of DJP Online application users, especially MSMEs, using the End-User Computing Satisfaction (EUCS) and Importance Performance Analysis (IPA) methods. The objects of this study were 120 MSME taxpayers in the West Java III Regional Office, namely Bogor City, Depok City, Bekasi City and Bogor Regency. This study uses the EUCS method to determine the attributes of the research questionnaire. The variables used are content, accuracy, format, ease of use and timeliness. The sampling technique is purposive sampling. The analysis tools used are Validity Test, Reliability Test and Importance Performance Analysis (IPA). IPA is used to calculate data from the questionnaire and find out which attributes need improvement. The results of the study indicate that users of the DJP Online application, especially MSME Taxpayers, are satisfied with the quality of services provided and meet user expectations, but still need to be improved. This can be seen from the average value of the suitability analysis and the Gap value which shows that the existing features and services have met user expectations. The attribute of the EUCS which is the main priority (Quadrant I) is 1, namely C1 (Content variable) containing Information provided in the DJP Online application regarding specific topics, for example: reporting of the UMKM Annual Tax Return is very relevant to my needs as an UMKM taxpayer.